Pengaruh Non Performing Loan (NPL), Loan to Deposit Ratio (LDR), Biaya Operasional dan Pendapatan Operasional (BOPO) Terhadap Profitabilitas Bank Umum Periode Tahun 2014-2021 - Jhony Aditya; Dewa Putu Yudi Pardita; I Ketut Darma (Program Studi Ekonomi Pembangunan, Fakultas Ekonomi, Universitas Warmadewa, 2023)
This research is conducted based on the research gap on the differences of opinion about Non Performing Loans, Loan to Deposit Ratio, Operating Expenses and Operating Income towards Profitability (ROA) from previous studies. The phenomenon gap that occurs in foreign banks in Indonesia is related to profitability (ROA) which affects the bank's performance. This study aims to determine the influence of Non Performing Loans, Loan to Deposit Ratio, Operating Expenses and Operating Income on profitability, both partially and simultaneously, in the foreign banking sector in Indonesia from 2014 to 2022. The research method used a quantitative approach, with the sample taken using purposive sampling technique, and the sample size consisted of 4 foreign banks in Indonesia (Citybank, Cimbniaga, Commonwealth, and Maybank). The results of the study using panel data analysis and hypothesis testing (t and f) show that (1) Non Performing Loans (NPL) have a negative and insignificant effect on profitability (ROA), (2) Loan to Deposit Ratio (LDR) has a positive and significant effect on profitability (ROA), (3) Operating Expenses and Operating Income (BOPO) have a negative and significant effect on profitability (ROA), and (4) NPL, LDR, and BOPO have a significant effect on profitability (ROA).